Durability of a small agricultural engine on biogas/diesel dual fuel operation - Tippayawong N. (2014)
Biogas from anaerobic digestion of organic waste is a potential alternative to the partial substitution of petroleum derived fuels because it is from renewable resources that are widely available. The effect of long term durability tests using biogas/diesel dual fuel operation on wear characteristics is evaluated and presented in this paper. Steady state tests were performed on a small, single cylinder, naturally aspirated, 4-stroke, direct injection diesel engine at a speed of 1500 rpm, coupled to a generator set to generate electricity for over 3500 hours. Lubricating oil samples were collected during the test run and were subjected to the analysis of various wear metal traces present and the changes in their properties. After completion of the endurance test, the engine was dismantled for physical inspection and wear assessment of vital parts. Formation of carbon deposits on in-cylinder surfaces was not found to be problematic. Injector tip coking did not occur. Surface wear and accumulations of metal debris in crankcase lubricating oil samples were analyzed and found to increase with time, but not at an unusual rate. Properties of used lubricating oils did not alter significantly from their original values. Wear was not significantly different in the test engine fueled with the biogas/diesel combination. An overall evaluation of the results indicated that the biogas/diesel duel fuel operation could be substituted for diesel fuel in electricity generation and worked satisfactorily under long term engine operation without any major troubles. © Shiraz University.